PENGARUH PERPUTARAN MODAL KERJA TERHADAP PROFITABILITAS PADA PERUSAHAAN KIMIA FARMA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Irvan Kharis Arviana; Risal Rinofah; Pristin Prima Sari (Journal Of Business, Finance, and Economics (JBFE), 2020)
This study is aimed to analyze the impact of cash turnover, receivable turnover, and inventory turnover to profitability of kimia farma companies that are registered in BEI at sector Farmasi 2012 – 2016 years. This study is correlational. The object of this study is kimia farma  companies that are registered in Bursa Efek Indonesia (BEI). The sampling method that is used in this study is judgement sampling. The data is obtained by documenting data from Bursa Efek Indonesia. Data regression with SPSS program version 16.0 is being used to analyze all of data.The study with PT. Kimia Farma, Tbk as the object shows that the cash turnover, receivable turnover, and inventory turnover  simultaneously affected the profitability. Partially, all the cash turnover variable (X1) significantly give positive impact to the profitability. On the other hand, the receivable turnover (X2) significantly give positive impact to the profitability. Last, the inventory turnover give significantly positive impact to the  profitability.Key Words: Cash turnover, Receivable turnover, Inventory turnover and  Profitability.